2019
DOI: 10.1038/s41467-019-11513-1
|View full text |Cite
|
Sign up to set email alerts
|

Angptl8 mediates food-driven resetting of hepatic circadian clock in mice

Abstract: Diurnal light-dark cycle resets the master clock, while timed food intake is another potent synchronizer of peripheral clocks in mammals. As the largest metabolic organ, the liver sensitively responds to the food signals and secretes hepatokines, leading to the robust regulation of metabolic and clock processes. However, it remains unknown which hepatokine mediates the food-driven resetting of the liver clock independent of the master clock. Here, we identify Angptl8 as a hepatokine that resets diurnal rhythms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 71 publications
(79 reference statements)
5
40
0
Order By: Relevance
“…However, RT-qPCR results illustrated that there were strong daily fluctuations in the expression of Scd1 and Scd2. Our pervious study illustrated the circadian rhythm of Angptl8 [27]. The presented study further revealed the circadian rhythm of Angptl3 and Angptl4, which oscillated both under LD and L-DD.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…However, RT-qPCR results illustrated that there were strong daily fluctuations in the expression of Scd1 and Scd2. Our pervious study illustrated the circadian rhythm of Angptl8 [27]. The presented study further revealed the circadian rhythm of Angptl3 and Angptl4, which oscillated both under LD and L-DD.…”
Section: Discussionsupporting
confidence: 71%
“…The present study extended our recent publication [27], and screened the oscillation gene in mouse liver under L-DD through MetaCycle. Approximatively 12.1% of the genes exhibited 24 h oscillation under L-DD.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations